Sustainable wastewater treatment solutions for rural communities': Public (centralized) or individual (on-site). Case study - Joanna Boguniewicz-Zabłocka; Andrea G. Capodaglio (Economic and Environmental Studies (E&ES), 2017)
The implementation of Water Framework Directive, speaking about the need to achieve good water status, and thus the corresponding sewage treatment caused the problem of waste water management has become a very important starting from the municipal level, through the national and the European ending. Sustainability, although not explicitly mentioned in the relevant EU or national legislation, it is key to implement wastewater systems. Their main objectives are to protect and promote human health by providing a clean environment, and breaking the cycle of disease. In this paper sustainability of wastewater collection and treatment options in the rural communities' in Poland, are discussed in the context of recent infrastructure investments. The paper presents an attempt to evaluate the implemented solutions for wastewater management in rural areas considering sustainable development criteria. Advantages and disadvantages of proposed system has been analysed with the focus to the question of selecting the right strategy that would fulfil both population and environmental needs.
Keywords: Q56; Q53; 330; wastewater treatment plant; sustainability criteria; local sanitation system